2018
DOI: 10.1007/s12272-018-1034-2
|View full text |Cite
|
Sign up to set email alerts
|

Two new β-carboline alkaloids from the stems of Picrasma quassioides

Abstract: Two new β-carboline alkaloids, 1-acetyl-4-methoxy-8-hydroxy-β-carboline (1) and 1-acetyl-4,8-dimethoxy-β-carboline (2), together with 10 known compounds; seven β-carboline alkaloids (3-9), two canthin-6-one alkaloids (10 and 11), and one quassinoid (12) were isolated from the stems of Picrasma quassioides. The structure of the new compounds 1 and 2 were determined by spectroscopic analyses including 1D- and 2D-NMR and HRMS interpretation. All the isolates (1-12) were evaluated for their cytotoxicity against hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…There are a wide‐range of evidence suggesting that bioactive compounds isolated from Picrasma quassioides have significant anti‐proliferative effects on different types of cancer cells, including hepatic, ovarian, and gastric carcinomas 23–26 . Moreover, ethanol extract of Picrasma quassioides has been found to reduce the migration of H‐RAS mutated hepatic cancer cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…There are a wide‐range of evidence suggesting that bioactive compounds isolated from Picrasma quassioides have significant anti‐proliferative effects on different types of cancer cells, including hepatic, ovarian, and gastric carcinomas 23–26 . Moreover, ethanol extract of Picrasma quassioides has been found to reduce the migration of H‐RAS mutated hepatic cancer cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…4-Methoxy-1-vinyl-β-carboline and 1-methoxy-β-carboline are cytotoxic to A2780 and SKOV3 human ovarian cancer cells and exhibited excellent antitumor activity (67). β-carboline-1-carboxylic acid, isolated from the stem of P. quassioides, demonstrated moderate inhibitory activities against K562 leukemia cancer cells and SGC-7901 human gastric cancer cells (68) (Table VII).…”
Section: A N T I C a N C E R E F F E C T S O F β -C A Rb O L I N E A L K A L O I D Smentioning
confidence: 99%
“…However, as an Asian traditional medicine, P. quassioides exerts its effects via individual chemical components and through synergistic effects of several compounds. Modern clinical research indicated that P. quassioides has a significant effect on hypertension (32), pneumonia (67,88), dysentery (89) and other disease symptoms (90,91). Previous studies have also developed various preparations and drugs using P. quassioides, such as Kumu injection, Xiaoyan Lidan tablet (92), Fufang Kumu Xiaoyan capsule (93) and Fufang Kumu Xiaoyan tablet (94).…”
Section: Clinical Applications and Developmental Prospects Of Picrasma Quassioides (D Don) Bennmentioning
confidence: 99%
“…Moreover, dehydrocrenatidine ( 31 ) was effective against A2780 cells with an IC 50 of 2.02 ± 0.95 μM and against SKOV3 cells at an IC 50 of 11.89 ± 2.38 μM. Meanwhile, nigakinone ( 25 ) and methylnigakinone ( 26 ) were also effective against HepG2 cancer cells [ 3 , 55 , 56 ].…”
Section: Pharmacological Activities Of Picrasma Quassioimentioning
confidence: 99%